2016
DOI: 10.1007/s11071-016-2870-6
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting attractors in a memcapacitor-based chaotic oscillator

Abstract: In this paper, a smooth curve model of memcapacitor and its equivalent circuit are designed. Based on this memcapacitor, a novel memcapacitive chaotic circuit is presented. Dynamical behaviors of the circuit with various parameters are investigated both theoretically and experimentally. The numerical results indicate that the circuit displays complex nonlinear properties including coexisting and symmetrical bifurcations. The main characteristic of this memcapacitive chaotic circuit is the various coexisting at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…On the other hand, coexisting chaotic attractors have been reported in many nonlinear systems in the recent years [19][20][21][22][23]. In [20,21], the coexisting chaotic attractors were found in some 4D smooth systems, and there are overlaps between the coexisting chaotic attractors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, coexisting chaotic attractors have been reported in many nonlinear systems in the recent years [19][20][21][22][23]. In [20,21], the coexisting chaotic attractors were found in some 4D smooth systems, and there are overlaps between the coexisting chaotic attractors.…”
Section: Introductionmentioning
confidence: 99%
“…In [20,21], the coexisting chaotic attractors were found in some 4D smooth systems, and there are overlaps between the coexisting chaotic attractors. In [22], Kengne et al reported a simple 3D autonomous jerk system with multiple attractors; the chaotic system in [22] belongs to the generalized Lü chaotic system family.…”
Section: Introductionmentioning
confidence: 99%
“…There are overlaps between the coexisting chaotic attractors in [3][4][5][7][8][9]. However, there are two isolated chaotic attractors in fractional-order chaotic system (2); that is, there are no overlaps between the coexisting chaotic attractors in fractional-order chaotic system (2).…”
Section: Remarkmentioning
confidence: 99%
“…The high irregularity, unpredictability, and complexity in chaotic systems [1,2] have been widely used in the field of engineering and technology such as secure communications, image steganography, authenticated encryption, motor control, and power system protection. Recently, coexisting chaotic attractors have been found in chaotic systems [3][4][5][6][7][8][9]. For example, the coexisting chaotic attractors in a 3D no-equilibrium system were reported by Pham et al [3], the coexisting multiple attractors in Hopfield neural network were found by Bao et al [4], the coexisting chaotic attractors in a hyperchaotic hyperjerk system were given by Wang et al [5], the coexisting "positive attractor" and "negative attractor" in a 3D autonomous continuous chaotic system were found by Zhou and Ke [6], and so on [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…So several memcapacitor models, including piecewise linear, quadric and cubic function models, memristor-based memcapacitor models, and memcapacitor emulators, were proposed in [16][17][18][19][20][21], and a mathematical memcapacitor model and a corresponding circuit model are established in [22]. Some special phenomena such as hidden attractors, coexistence attractors, and extreme multistability were found in memcapacitorbased chaotic oscillators [23,24] and memristor-based chaotic oscillators [25][26][27]. In fact, multistability and coexisting attractors have caught the attention of researcher in general chaotic systems [28][29][30].…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%